Validation of a Psychosocial Chronic Stress Model in the Pig Using a Multidisciplinary Approach at the Gut-Brain and Behavior Levels - Menneson, Sophie; Ménicot, Samuel; Ferret-Bernard, Stéphanie; Guérin, Sylvie; Romé, Véronique; Le Normand, Laurence; Randuineau, Gwénaëlle; Gambarota, Giulio; Noirot, Virginie; Etienne, Pierre; Coquery, Nicolas; Val-Laillet, David (Frontiers in Behavioral Neuroscience, 2019)
Psychological chronic stress is an important risk factor for major depressive disorder, of which consequences have been widely studied in rodent models. The present work aimed at describing a pig model of chronic stress based on social isolation, environmental impoverishment and unpredictability. Three groups of animals of both sexes were constituted. One was exposed to the psychosocial stressors (SC, n=22), a second was exposed similarly and received the antidepressant fluoxetine (SF, n=12), and a third group (NSC, n=22) remained unstressed. Behavior was evaluated in home pens and during dedicated tests to assess resignation- and anxiety-like behavior. Salivary cortisol, fecal short-chain fatty acids (SCFAs), and various plasma and intestinal biomarkers were analyzed. Brain function and structure were evaluated via fMRI, proton MRS and molecular biology in the hippocampus, and immunodetection of DCX-positive cells in the dentate gyrus. SC showed more resignation (SC/NSC, p=0.02) and had a higher level of salivary cortisol (SC/NSC: p<0.05). Hippocampal neuronal density, responses to a novel odor and levels of BDNF and 5-HT1AR were lower, and the number of DCX-positive cells was higher in SC compared to NSC. In SC, HOMA-IR was higher (p<0.001) and microbiota activity was lower (SCFAs, SC/NSC: p<0.01). Exposure to psychosocial stressors in the pig model induced effects consistent with the human and rodent literature, and fluoxetine partially or totally reversed several of these effects. This model would open the way to innovative translational research exploring the mechanisms of chronic stress and testing intervention strategies with good face validity related to human.